Multianalyte serology in home-sampled blood enables an unbiased assessment of the immune response against SARS-CoV-2 - Roxhed, Niclas; Bendes, Annika; Dale, Matilda; Mattsson, Cecilia; Hanke, Leo; Dodig-Crnkovic, Tea; Murray, Christian; Meineke, Birthe; Elsässer, Simon; Andrell, Juni; Haverall, Sebastian; Thålin, Charlotte; et al. (Royal Institute of Technology, 2021)
Dried blood spot (DBS) samples were collected during spring of 2020 from random and undiagnosed individuals in Stockholm, Sweden.
Receiving DBS from 878 participants, we applied multiplexed serology assays to determine IgG and IgM levels against several versions of SARS-CoV-2 proteins (S, RBD, N).
The data reports anonymised an normalised "relative antibody titers" obtained in the eluates of the DBS samples. The data can be made available for validation purposes and upon reasonable request.
A reasonable request should contain:1) Name of PI and host organisation2) Contact details3) Scientific purpose of data access request4) Commitment to inform when the data has been used in a publication5) Commitment not to host or share the data outside the requesting organisation6) Statement of non-commercial use of data
Keywords: Infectious diseases; Medical and Health Sciences; Medicin och hälsovetenskap; Infectious Medicine; Infektionsmedicin